1998
DOI: 10.1089/ten.1998.4.415
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenic Differentiation of Cultured Human Mesenchymal Stem Cells from Marrow

Abstract: In the adult human, mesenchymal stem cells (MSCs) resident in bone marrow retain the capacity to proliferate and differentiate along multiple connective tissue lineages, including cartilage. In this study, culture-expanded human MSCs (hMSCs) of 60 human donors were induced to express the morphology and gene products of chondrocytes. Chondrogenesis was induced by culturing hMSCs in micromass pellets in the presence of a defined medium that included 100 nM dexamethasone and 10 ng/ml transforming growth factor-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
932
2
15

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 1,190 publications
(983 citation statements)
references
References 49 publications
34
932
2
15
Order By: Relevance
“…The data demonstrated that sustained expression of TGF-β1 is more effective in inducing chondrogenic differentiation of human MSCs than IGF-1. Previous studies using TGF-β1 to induce chondrogenesis in MSC was done by addition of TGF-β1 protein [8,21,24]. The optimal concentration of TGF-β1 used in the protein form to induce chondrogenesis in MSCs was 10 ng/mL [21,24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The data demonstrated that sustained expression of TGF-β1 is more effective in inducing chondrogenic differentiation of human MSCs than IGF-1. Previous studies using TGF-β1 to induce chondrogenesis in MSC was done by addition of TGF-β1 protein [8,21,24]. The optimal concentration of TGF-β1 used in the protein form to induce chondrogenesis in MSCs was 10 ng/mL [21,24].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using TGF-β1 to induce chondrogenesis in MSC was done by addition of TGF-β1 protein [8,21,24]. The optimal concentration of TGF-β1 used in the protein form to induce chondrogenesis in MSCs was 10 ng/mL [21,24]. Interestingly, the results of ELISA showed that chondrogenic differentiation was more evident in pellets made from cells transduced with AdTGF-β1 at 50 MOI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bone marrow mesenchymal stem cells (MSCs) are currently among the best characterized adult stem cells (Majumdar et al, 1998;Pittenger et al, 1999) isolated from various tissue sources such as fat, muscle, and bone (Jiang et al, 2002b;Sottile et al, 2002;Zuk et al, 2002). These cells are able to differentiate into bone, fat, cartilage, muscle tissue, and neurons (Mackay et al, 1998;Reyes et al, 2001;Sekiya et al, 2004;Woodbury et al, 2000) and were ultimately reported in almost all cell lineages (Jiang et al, 2002;Krause et al, 2001). For these reasons, the isolation and manipulation of adult stem cells represents a promising tool for understanding tissue development and regeneration, as well as for studying the engineered repair of tissues and organs (Orlic et al, 2001;Pittenger and Martin, 2004;Wakitani et al, 2002).…”
Section: Introductionmentioning
confidence: 99%